2002
DOI: 10.1021/jo026086r
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Decomposition of Potassium Alkalide−Lipophilic Crown Ether Complexes in Tetrahydrofuran

Abstract: Cyclohexano-15-crown-5, cyclohexano-18-crown-6, dicyclohexano-15-crown-5, and dicyclohexano-18-crown-6, but not dicylohexano-16-crown-5, in THF dissolve potassium metal to form dark blue potassium alkalide solutions at ambient temperature. On standing, the potassium alkalide complexes decompose and the solutions turn colorless at differing rates. Identification of the products provides insight into the decomposition mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
3
25
1
Order By: Relevance
“…The direction of the ether bond cleavage depended on the kind of substituent. Unexpectedly, the scission of one of the linear ether bonds was found in some oxiranes possessing an oxygen atom in the substituent [7]. The highly strained oxirane ring remained undisturbed.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The direction of the ether bond cleavage depended on the kind of substituent. Unexpectedly, the scission of one of the linear ether bonds was found in some oxiranes possessing an oxygen atom in the substituent [7]. The highly strained oxirane ring remained undisturbed.…”
Section: Introductionmentioning
confidence: 99%
“…Then, it was found that the regioselective cleavage of the alkyl-oxygen bond occurred also in methyl phenyl ether, ethyl phenyl ether [2], and allyl phenyl ether [3] in their reactions with K À , K þ (15-crown-5) 2 1. It was shown in further works that various cyclic ethers as monosubstituted oxiranes [3][4][5][6][7][8][9], oxetane [10][11][12] and tetrahydrofuran [13,14] can also be opened by alkalides. The most interesting seemed to be the reaction involving oxiranes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[68][69][70][71] Similarly, potassium anions cleave exclusively the allyl-oxygen or benzyl-oxygen bond in some glycidyl ethers to give organopotassium compounds as intermediate reaction products. [72,73] The classical methods of allyl ether deprotection generally proceed through double-bond isomerization to enol ethers by potassium tert-butoxide [74] or rhenium complexes followed by acidic hydrolysis. [75,76] In the case of the electrochemical procedure a mechanism involving the allyl-oxygen cleavage with formation of a π-allylnickel intermediate has been suggested.…”
Section: Electrochemical Methodsmentioning
confidence: 99%